Trends in cereal supply, demand, trade, and stocks - Paulino, Leonardo A. (International Food Policy Research Institute, 1988)
Forces underlying commodity trade, capital movement, technology transfer, and political cooperation contribute to increased interdependence among nations. The policies of a country are influenced by the international policy environment, which represents the collective national policies of other countries. Thus, depending on the policy area, countries affect one another in varying degrees. This chapter discusses the past, present, and emerging global conditions of the supply and demand for cereals, an important element of agriculture and trade in this international environment. These global conditions constitute a crucial part of the framework of agricultural policies of developing countries. A global backdrop is provided here for the chapters that address domestic aspects of price policies.